Gaps in policy-relevant information on burden of disease in children: a systematic review - Rudan, Igor; Lawn, Joy; Cousens, Simon; Rowe, Alexander K; Boschi-Pinto, Cynthia; Tomašković, Lana; Mendoza, Walter; Lanata, Claudio F; Roca-Feltrer, Arantxa; Carneiro, Ilona; Schellenberg, Joanna A; Polašek, Ozren; et al. (The Lancet (British edition), 2005)
Valid information about cause-specific child mortality and morbidity is an essential foundation for national and international health policy. We undertook a systematic review to investigate the geographical dispersion of and time trends in publication for policy-relevant information about children's health and to assess associations between the availability of reliable data and poverty. We identified data available on Jan 1, 2001, and published since 1980, for the major causes of morbidity and mortality in young children. Studies with relevant data were assessed against a set of inclusion criteria to identify those likely to provide unbiased estimates of the burden of childhood disease in the community. Only 308 information units from more than 17 000 papers identified were regarded as possible unbiased sources for estimates of childhood disease burden. The geographical distribution of these information units revealed a pattern of small well-researched populations surrounded by large areas with little available information. No reliable population-based data were identified from many of the world's poorest countries, which account for about a third of all deaths of children worldwide. The number of new studies diminished over the last 10 years investigated. The number of population-based studies yielding estimates of burden of childhood disease from less developed countries was low. The decreasing trend over time suggests reductions in research investment in this sphere. Data are especially sparse from the world's least developed countries with the highest child mortality. Guidelines are needed for the conduct of burden-of-disease studies together with an international research policy that gives increased emphasis to global equity and coverage so that knowledge can be generated from all regions of the world.